Anemia in Children with Down Syndrome - Ariel Tenenbaum; Sarah Malkiel; Isaiah D. Wexler; Floris Levy-Khademi; Shoshana Revel-Vilk; Polina Stepensky (International Journal of Pediatrics)
Background. Iron deficiency anemia impacts on cognitive development. The objective of this study was to determine the prevalence of anemia and iron deficiency in children with Down syndrome and identify risk factors for anemia. Methods. We conducted a prolective cross-sectional study of children attending a multidisciplinary Down syndrome medical center. One hundred and forty nine children with Down syndrome aged 0–20 years were enrolled in the study. Information obtained included a medical history, physical and developmental examination, nutritional assessment, and the results of blood tests. Results. Of the patients studied, 8.1% were found to have anemia. Among the 38 children who had iron studies, 50.0% had iron deficiency. In a multivariate analysis, Arab ethnicity and low weight for age were significantly associated with anemia. Gender, height, the presence of an eating disorder, and congenital heart disease were not risk factors for anemia. Conclusions. Children with Down syndrome are at risk for anemia and iron deficiency similar to the general population. Children with Down syndrome should be monitored for anemia and iron deficiency so that prompt intervention can be initiated.